Peran arsiparis dalam optimalisasi kearsipan di Fakultas Ekonomi dan Bisnis Universitas Padjadjaran - Meva, Titis Ardia; Sukaesih, Sukaesih; Sujana, Lusi Romaddyniah (Faculty of Communication, Padjadjaran University, 2024)
This study examines the vital role of archivists in records management at the Faculty of Economics and Business, Universitas Padjadjaran (FEB Unpad). The primary focus is evaluating archivists' contributions throughout the records lifecycle and analyzing the competencies required to enhance the effectiveness and efficiency of records management. The research employs a qualitative approach with a descriptive method. Data collection involves in-depth interviews, observation, documentation, and literature review. Two informants were selected based on a minimum of 5 years of experience in archival work. Data analysis utilizes thematic analysis techniques. Findings indicate archivists' crucial role in all stages of the records lifecycle, including creation, distribution, use, maintenance, and disposal. Required competencies encompass technical, professional, personal, and social aspects. The study identifies challenges in archival activities at FEB Unpad, including human resource limitations and technical issues with the digital archiving system